Readability of Articles in Journal of Religious and Socio-cultural Studies - Ai Yeni Yuliyanti; Busro Busro (Langkawi: Journal of The Association for Arabic and English, 2021)
Although the research on the readability of particular text has been extensively undertaken, little research applied to article journals. This study attempts to analyze the readability of religious and socio-cultural articles published in the Wawasan Journal. It is crucial to analyze it to prepare the journal indexed by Scopus at the international level and Sinta 1 at the national level. This study adopted the mixed method, quantitative to count the readability score, and qualitative to describe the readability score.  Data were collected from three issues: Volume 4, no 1 (2019), Volume 4, no 2 (2019), and Volume 5, no 1 (2020) because the journal uses English in those issues. Then, a test was undertaken by use of online software https://readabilityformulas.com on the texts of each article. The readability formulas are FKGL, CLI, SMOG, ARI, and LWF. The result shows that most articles of Wawasan Journal are appropriate with the targeted readers: college, college graduate, and college graduate and above. Nevertheless, many articles are still regarded as suitable for the lower level, namely school grade level. Based on the readability score average of three issues is relatively stable. Due to FKGL, CLI, SMOG, and ARI formulas, the three issues are appropriate at college level. Meanwhile, those are appropriate with college graduates and above based on LWF. It is still found inappropriate text with targeted readers, the researchers suggest that the editorial board need to check not only its originality and grammar but also the readability score of the proposed article.